Carbon dynamics of a warm season turfgrass using the eddy-covariance technique - Pahari, Roshani; Leclerc, Monique Y.; Zhang, Gengsheng; Nahrawi, Hafsah; Raymer, Paul L. (Elsevier B.V., 2018)
Despite their ubiquitous presence in the urban landscape throughout the United States, scant attention has been given to evaluate the magnitude of net carbon balance from turfgrasses. Warm season turfgrasses, in particular, have largely been understudied for their carbon sequestration potential. With questions being frequently raised on the environment friendliness of warm season turfgrasses, detailed and robust studies focusing on the carbon behavior of such systems are warranted. This study delves into the carbon balance of ‘Tifway’ bermudagrass, the extensively used warm-season turfgrass in Georgia and other subtropical and warm temperate areas. Using the eddy-covariance method, the amount of CO2 captured by a highly managed turfgrass system was measured by deploying two eddy-covariance systems for the study period of 31 months. The results show that ‘Tifway’ bermudagrass is a net sink of carbon, sequestering it at the rate of 4.51–5.15 Mg C ha−1 yr−1. The turf canopy as well as management activities carried out in the farm appear to have a powerful influence on the carbon behavior of the turf. Seasonal and monthly fluxes suggest that turf is an efficient assimilator of carbon during its active growth period of summer and fall months. The results show that the turf sequestered higher amounts of carbon than many agricultural crop systems, supporting the assertion that it is an efficient assimilator of atmospheric carbon. © 2017